The Impact Of Gender Equality Policies On Socio-Economic Transformations (On The Example Of Uzbekistan) (Eurasian Journal of History, Geography and Economics, 2026)
This study examines the impact of gender equality policy on socio-economic transformations, using Uzbekistan as a case study. It analyzes how state policies aimed at ensuring gender equality influence economic development, labor market participation, education access, and social welfare. The research also explores institutional reforms, legal frameworks, and social programs implemented to reduce gender disparities. Particular attention is given to the relationship between gender equality and sustainable development, as well as the challenges faced in the practical implementation of gender policies. The findings highlight that gender equality is a key factor in achieving inclusive socio-economic growth and improving overall societal well-being.